Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/00268976.2010.510805
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of OCS and their reaction with H2O on singlet potential energy surface

Abstract: The isomers of the carbonyl sulfide (OCS) molecule are investigated in detail at CCSD(T)/cc-pVTZ//MP2/6-311þþG(2d,2p) level of theory. One cyclic isomer was identified along with three different linear minima of the OCS molecule. Three interconversion transition states were also located between cyclic and linear forms of OCS. Among these four isomers, the singlet potential energy surface (PES) for the molecule-molecule reaction between the three most energetically favoured isomers of OCS and H 2 O has been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several theoretical studies have been carried out on the 1:1 complex. [3][4][5][6][7][8][9][10] However, a disagreement exists on the different possible isomers (structures F1, F2, and F3 of Fig. 8).…”
Section: A Ocs-h 2 O Complexmentioning
confidence: 99%
See 4 more Smart Citations
“…Several theoretical studies have been carried out on the 1:1 complex. [3][4][5][6][7][8][9][10] However, a disagreement exists on the different possible isomers (structures F1, F2, and F3 of Fig. 8).…”
Section: A Ocs-h 2 O Complexmentioning
confidence: 99%
“…3 Tatamitani and Ogata 10 Ghosh et al found the F1 and F2 structures [CCSD(T)/cc-pvTZ single point at MP2/6-311++G(2d,2p) geometries]. 6 In agreement with the work of Hartt et al 4 our MP2/AVTZ calculations lead to the three structures with D e values of 8.6, 8.9, and 8.7 kJ/mol and D 0 values of 6.6, 5.5, and 5.1 kJ/mol for F1, F2, and F3, respectively. However, the F3 structure seems to be an artefact of MP2 because all optimisations of this geometry at the higher level of theory CCSD(T)-F12a/AVTZ lead to the nearest stable structure F2.…”
Section: A Ocs-h 2 O Complexmentioning
confidence: 99%
See 3 more Smart Citations